2000
DOI: 10.1034/j.1600-0609.2000.90106.x
|View full text |Cite
|
Sign up to set email alerts
|

Relation of ferritin levels to pulmonary function in patients with thalassemia major and the acute effects of transfusion

Abstract: We studied 36 patients (17 males and 19 females) with thalassemia major by performing pulmonary function testing (PFT), arterial blood gas analysis (ABG), as well as determining the serum ferritin level. In addition, 19 of these patients were transfused with two units of packed cells, and a repeat ABG and PFT were performed. Twenty-three patients had normal PFTs, eleven patients (30.6%) showed a restrictive pattern (significant decrease in both TLC and DLCO), and only two patients (5.6%) showed an obstructive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
35
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 3 publications
5
35
1
3
Order By: Relevance
“…According to our results, restrictive pattern was the most common finding (72.7%) in PFT, which is similar to other studies [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. As the data show, iron accumulation because of repeated transfusion has been proposed as the likely mechanism that causes pulmonary dysfunction in thalassemic patients [5,8,11,13,15,17].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…According to our results, restrictive pattern was the most common finding (72.7%) in PFT, which is similar to other studies [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. As the data show, iron accumulation because of repeated transfusion has been proposed as the likely mechanism that causes pulmonary dysfunction in thalassemic patients [5,8,11,13,15,17].…”
Section: Discussionsupporting
confidence: 93%
“…As the data show, iron accumulation because of repeated transfusion has been proposed as the likely mechanism that causes pulmonary dysfunction in thalassemic patients [5,8,11,13,15,17]. In the study by Parakh and colleagues for finding the pathogenesis of respiratory impairment in thalassaemia patients, PFT and carbon monoxide diffusion capacity (DLco) were done for 31 patients over 8 years.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This is similar to other published studies done by Rahim et al 4 and Bourli et al 6 where restrictive abnormalities were most frequently reported. Studies done by Kanj et al 4 and Amin et al 7 showed both Obstructive and Restrictive pattern of Respiratory dysfunction.…”
Section: Discussionsupporting
confidence: 82%